Extended-Spectrum Beta-Lactamase-Producing Gram-Negative Bacteria on Healthcare Workers’ Mobile Phones: Evidence from Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Araya S; Desta K; Woldeamanuel Y (Dove Medical Press, 2021)
Shambel Araya,1 Kassu Desta,1 Yimtubezinash Woldeamanuel2 1Department of Medical Laboratory Sciences, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Medical Microbiology, Immunology and Parasitology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Shambel Araya Tel: +251939459529Email shambelaraya8@gmail.comBackground: Mobile phones are widely used in hospital settings for different purposes. Mobile phones of healthcare workers (HCWs) could be colonized or harbor extended-spectrum beta-lactamase (ESBL) producing gram-negative bacteria and may act as source of infectious agents. The aim of this study was to determine the rate of extended-spectrum beta-lactamase-producing Gram-negative bacteria on mobile phones of healthcare workers, to assess their antimicrobial susceptibility patterns and associated factors.Methods: A laboratory-based cross-sectional study was conducted involving a total of 572 samples by rubbing swabs of the front screen, back, keypad, and metallic surfaces of mobile phones of healthcare workers using simple random sampling technique. All specimens were screened for ESBL using ESBL CHROME agar and confirmed using double-disk diffusion test (DDDT). Antibiotic susceptibility testing was done by the Kirby–Bauer disk diffusion technique on Mueller–Hinton agar. Data were analyzed using SPSS version 25, odds ratio and p-value was calculated to determine the association among variables.Results: Overall, the number of mobile phones contaminated by gram-negative bacteria was 454 out of 572 (79.4%). Female sex (OR 0.651, p-value=0.039) and service year (OR 0.468, p-value=0.038) of healthcare workers were found to be the most significant factors associated with healthcare professionals’ mobile phone and bacterial contamination. Nine percent of the isolates were ESBL-producers. K. pneumoniae (27%) was the dominant ESBL-producing isolate followed by Acinetobacter spp. (14.5%) and E.coli (14.5%). ESBL-producers were highly resistant to ampicillin (95.8%), piperacillin (83.3%), cotrimoxazole (70.8%), and chloramphenicol (54.2%), but highly sensitive to meropenem (87.5%), amikacin (85.4%), and piperacillin-tazobactam (81.2%).Conclusion: ESBL-producing Gram-negative bacteria were isolated from 8.3% of HCWs’ mobile phones. As high as 79.4% of the isolates were multidrug resistant. Mobile phones can lead to bacterial cross-contamination and could be a source of nosocomial infections.Keywords: mobile phones, extended-spectrum β-lactamase, Gram-negative bacteria, hospital-acquired infection, Addis Ababa, Ethiopia